2019
DOI: 10.1152/ajpendo.00377.2018
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity counteracts metabolic syndrome-induced hypogonadotropic hypogonadism and erectile dysfunction in the rabbit

Abstract: Metabolic syndrome (MetS) clusters cardiovascular and metabolic risk factors along with hypogonadism and erectile dysfunction. Lifestyle modifications including physical exercise (PhyEx) are well-known treatments for this condition. In this study, we analyzed the effect of PhyEx on hypothalamic-pituitary-testis axis and erectile function by use of an animal MetS model, previously established in rabbits fed a high-fat diet (HFD). Rabbits fed a regular diet (RD) were used as controls. A subset of both groups was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 62 publications
4
42
0
Order By: Relevance
“…Interestingly, we recently demonstrated that, when HFD rabbits were trained with aerobic physical activity on a treadmill, they exhibited a reversal of the hypogonadotropic condition, including a restoration of the hypothalamic network controlling GnRH production. However, these animals also showed a deficient muscular response to fatigue, as demonstrated by a significant reduction of both running distance and running time in comparison to the control group fed a regular diet (Morelli et al 2019). Hence, they are less prone to perform physical exercise.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Interestingly, we recently demonstrated that, when HFD rabbits were trained with aerobic physical activity on a treadmill, they exhibited a reversal of the hypogonadotropic condition, including a restoration of the hypothalamic network controlling GnRH production. However, these animals also showed a deficient muscular response to fatigue, as demonstrated by a significant reduction of both running distance and running time in comparison to the control group fed a regular diet (Morelli et al 2019). Hence, they are less prone to perform physical exercise.…”
Section: Introductionmentioning
confidence: 93%
“…; RD + testosterone group, n = 8) for 12 weeks. A subset of rabbits for each group (RD, n = 10; HFD, n = 12; HFD + testosterone, n = 10; RD + testosterone n = 4) was trained with a physical exercise (PhyEx) running protocol on a treadmill with increasing intensity, duration and frequency during the 12 weeks, as previously published (Morelli et al 2019) and described below. The remaining animals were left in the cages for the same period.…”
Section: Animals' Treatmentmentioning
confidence: 99%
See 3 more Smart Citations